FROM GUT TO BRAIN: THE ROLE OF FRUCTOOLIGOSACCHARIDES AND GALACTOOLIGOSACCHARIDES IN MODULATING THE GUT-BRAIN AXIS DURING EARLY CHILDHOOD - Addini Pascaramadhani; Rizky Prihandari; Rahayu Kania R; Hilna Khairunisa Shalihat (Journal of Indonesian Specialized Nutrition, 2026)
Background: The first five years of life are an essential stage during which the gut microbiota and the brain develop simultaneously. This development is mediated by the gut-brain axis (GBA), a bidirectional communication system operating through neural, endocrine, immune, and metabolic pathways. Fructooligosaccharides (FOS) and galactooligosaccharides (GOS) are well-researched prebiotics that promote beneficial gut bacteria producing neuroactive molecules such as short chain fatty acids, gamma-aminobutyric, and serotonin precursors, which are associated with neurotransmitter synthesis, blood-brain barrier function, HPA axis regulation, and neuroinflammation. Methods: This narrative review discusses the potential mechanisms by which FOS and GOS might affect gut-brain communication in early childhood, drawing from experimental animal studies and clinical trials in adults and children. Results: In animal models, FOS and GOS reduce anxiety and depression-like behaviors and may support cognitive function through SCFA-mediated effects on neurotransmitter modulation. Human pediatric evidence remains limited, though recent findings suggest GOS can lower emotional responsiveness and cortisol levels in school-age children. Conclusion: Important gaps remain, particularly the lack of long-term studies in children under five and insufficient data from low- and middle-income countries. Well-designed pediatric studies are needed to understand FOS and GOS effects on early brain development.